Muerte, muertos y “llanto” palero - Ana Stela de Almeida Cunha (Ateliers d'Anthropologie)
This paper describes some of the ceremonies that make up the ritual cycles surrounding the death of palo monte priests. They are known as llanto (moaning) and I will focus on the ethnography of two of these llantos—that of a palera who was also a spiritist and a santera (2007) and that of another palero who was also affiliated with other Cuban religious practices (2009). The death of a priest of palo (and more broadly of a practitioner of any Afro-Cuban religion) is always a chance to observe his involvement in a specific practice, as well as his possible trajectories in other Afro-Cuban religions. During funerals, the multiple religious identities of a deceased person become particularly visible, as they converge and interact through rituals. Since they draw attention to the whole initiatory and religious network to which the deceased person belonged, funerals are key moments for understanding Cuban religious diversity and the creative and sometimes innovative relationships that develop between different ‘traditions’, according to an individual’s conceptions and nieds. The paper offers a detailed description of the funeral ceremonies of palo monte and also highlights religious plurality, the delicate hierarchies that this implies, the transition from one practice to another—reflecting the lives of deceased paleros—as well as the dynamics of creativity at work. As emphasized by Bruner (1993) or Hallam and Ingold (2007), these dynamics stem from a process of natural development, under constant construction, in the lives of religious people and ‘believers’.